Exploring the experiences of children and youth with mobility impairments in four basic educational settings in Ghana - Nseibo, Job Kofi (Department of Health and Rehabilitation Sciences, 2021)
Education is a fundamental right for children all over the world. In Ghana, education for children with mobility impairments (MI) is one area that needs attention because little research has explored the experiences of these children and youth in basic educational settings. The research question that guided this research was: What are the educational experiences of children and youth with MI in education in Ghana? Understanding educational experiences of children and youth with MI will allow policymakers, the Ministry of Education, and educational researchers to develop educational support systems for children with MI. This is very important especially in the low-and-middle-income countries like Ghana where resources are limited. This study drew on three theoretical frameworks: Disability studies in education; Bronfenbrenner's ecological system theory and post-colonial theory. These theoretical frameworks guided the exploration of the educational experiences of children and youth with MI in four basic school settings (mainstream, inclusive, rehabilitation and special schools) with consideration to the implementation of inclusive education in Ghana. The child development and learning processes were researched in terms of complex systemic interactions between children with MI and their environment, and the advancement of liberation and the colonial legacy of the study in context. Data were drawn from 20 children with MI, from four head teachers and from 20 parents of children with MI through in-depth semi-structured interviews and focus group interviews. Thematic analysis was used to analyse the data. This study revealed inequities in the basic school curriculum within the four school settings. These inequities that existed in the school curriculum contributed to parents not achieving the expected results they had hoped for by sending their children to the rehabilitation centre and the special schools. This study also showed the inadequacy of the educational support systems (for example, student support teams, parents support teams, teacher support teams and education support teams) in the four educational settings. The study concludes that the absence of educational support systems contributed to the struggle that children with MI and their parents experienced during their children's educational trajectories. From the findings of this study, it is imperative to have further research to consider a general basic school curriculum to promote inclusivity in all four school settings. The study critically showed how the experiences of children and youth with MI were characterised by the inequity of basic school curriculum, negative attitude towards disability and the unavailability of an educational support system. This study also contributes towards the development of inclusive schooling practices in Ghana by providing a framework which promotes inclusion of children and youth with MI. The new knowledge not only adds to the limited literature on the educational experiences of children with MI, but also assists policymakers, stakeholders of education and researchers to promote practices that encourage inclusive education.